Review of the Technology, Development and Applications of Holographic Staring Radar - Rui GUO; Yue ZHANG; Biao TIAN; Yu XIAO; Jun HU; Shiyou XU; Zengping CHEN (Leida xuebao, 2023)
Holographic staring radar is an array radar that continuously looks everywhere and performs multiple functions simultaneously instead of sequentially. First, this paper clarifies the definition of holographic staring radar and summarizes the features, performance advantages, and accompanying risks of holographic staring radar. Then, the research history and main application directions of holographic staring radar are reviewed. Next, the holographic staring radar series of Sun Yat-sen University in China is introduced. The target detection results of this holographic staring radar are given, showing the application potential of a holographic staring radar system in low-altitude target monitoring. Next, the research progress of related key technologies is examined, including system design, beam control, target detection, and parameter estimation. Finally, the development trends of holographic staring radar are discussed.